2022
DOI: 10.1136/bmjopen-2021-056386
|View full text |Cite
|
Sign up to set email alerts
|

Explorative–descriptive study on the effects of COVID-19 on access to antiretroviral therapy services: the case of a teaching hospital in Ghana

Abstract: ObjectiveTo explore how the COVID-19 pandemic affected access to antiretroviral therapy (ART) services from the perspective of the persons living with HIV (PLWH).DesignThe study adopted an exploratory-descriptive qualitative design that used in-depth interviews as the technique for the data collection. Data analysis was done using conceptual content analysis, following the traditions of Elo and Kyngäs on deductive and Hsieh on inductive content analysis.SettingART clinic, Cape Coast Teaching Hospital, Ghana.Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…While increased structural barriers to accessing treatment (e.g., longer wait times) negatively impacted participant perceptions of care, reduced privacy during care interactions was described as the primary challenge negatively affecting the quality and breadth of clinical consultation. Broadly, findings align with those of qualitative studies conducted in other settings, which have identified both new and increased barriers for PWH during the pandemic 1417,19,20 and differ from prior qualitative work in South Africa, which was conducted within a program for highly adherent PWH. 13
Figure 1.Conceptual map of themes.
…”
Section: Discussionsupporting
confidence: 68%
“…While increased structural barriers to accessing treatment (e.g., longer wait times) negatively impacted participant perceptions of care, reduced privacy during care interactions was described as the primary challenge negatively affecting the quality and breadth of clinical consultation. Broadly, findings align with those of qualitative studies conducted in other settings, which have identified both new and increased barriers for PWH during the pandemic 1417,19,20 and differ from prior qualitative work in South Africa, which was conducted within a program for highly adherent PWH. 13
Figure 1.Conceptual map of themes.
…”
Section: Discussionsupporting
confidence: 68%
“…This phenomenon corroborates findings recorded among HIV patients. 29 If not checked, efforts made at achieving the Sustainable Development Goals (SDG) target 3.4 that seeks to promote life and health for persons living with non-communicable diseases (NCDs) through prevention and treatment 30 , 31 will be eroded.…”
Section: Discussionmentioning
confidence: 99%
“…Other barriers to health care access include decreased use of healthcare services due to country measures on elective care, fear of contagion and stigma; low health literacy [23,41], and inability to access services due to low socioeconomic status and poor competency to use technologies [35]. Prior studies indicated that people with needs for antiretroviral therapy [42], sexual and reproductive health services [43] and tuberculosis services [7,44] among others, had difficulty accessing services during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%